Axonal degeneration in an Alzheimer mouse model is PS1 gene dose dependent and linked to intraneuronal Aβ accumulation - Christensen, Ditte Z.; Huettenrauch, Melanie; Mitkovski, Miso; Pradier, Laurent; Wirths, Oliver (Frontiers in Aging Neuroscience, 2014)
Abnormalities and impairments in axonal transport are suggested to strongly contribute to the pathological alterations underlying AD. The exact mechanisms leading to axonopathy are currently unclear, but it was recently suggested that APP expression itself triggers axonal degeneration. We used APP transgenic mice and crossed them on a hemi- or homozygous PS1 knock-in background (APP/PS1KI). Depending on the mutant PS1 dosage, we demonstrate a clear aggravation in both plaque-associated and plaque-distant axonal degeneration, despite of an unchanged APP expression level. Amyloid-ß (Aβ) peptides were found to accumulate in axonal swellings as well as in axons and apical dendrites proximate to neurons accumulating intraneuronal Aβ in their cell bodies. This suggests that Aβ can be transported within neurites thereby contributing to axonal deficits. In addition, diffuse extracellular Aβ deposits were observed in the close vicinity of axonal spheroids accumulating intracellular Aβ, which might be indicative of a local Aβ release from sites of axonal damage.